The human capital and the obtainment of halal certification - Rafiki A.; Abdul Wahab K. (Emerald Group Publishing Ltd., 2024)
Purpose: This paper aims to analyse the relationship between human capital and obtainment of halal certification. Design/methodology/approach: The human capital theory is deployed as the basis to analyse the possible factors that determine the obtainment of halal certification by small firms. Four independent variables that were delineated include business experience, motivation, training and education. The proposed hypotheses mark the relationship between the four variables and the obtainment of the halal certification. The sample size (n = 370) is a group of small firms randomly picked from the four regions in the North Sumatera Province, Indonesia. Findings: By adopting the quantitative deductive-hypothetical method and the logistic regression analysis, the result has revealed that the aforementioned four variables have a significant relationship with the obtainment of halal certification. Originality/value: This paper provides the empirical findings and valuable insight for future researchers. The importance of obtaining the halal certification lies in not only more than convincing customers with the goodness of ingredient or compliance with the religions obligations but also it can serve as a strategy that brings a competitive advantage to the firms to grow. While the elements of human capital would be the factors that influence in the decision-making of obtaining the halal certification. 2016, Emerald Group Publishing Limited.